Rhodanese isozymes in three subjects with Leber's optic neuropathy. Issue 2 (February 1989) - Whitehouse, D B; Poole, C J; Kind, P R; Hopkinson, D A
Abstract : Previous studies have reported an association between Leber's optic neuropathy and deficiency of rhodanese activity in liver and rectal mucosa. We have studied the rhodanese isozymes in liver biopsies from three subjects with Leber's optic neuropathy. The rhodanese isozyme patterns were indistinguishable from controls both in relative intensity and position on the isoelectric focusing pH gradient. No new rhodanese isozymes were observed and there was no evidence of deficiency in any of the cases.